IMPLEMENTASI KONSEP TUJUAN HIDUP DAN MASYARAKAT SEBAGAI OBJEK KAJIAN DALAM FILSAFAT DARI PEMIKIRAN FILOSOF MUSLIM DI SDN 1 CIWALEN GARUT - Hermawan, Acep Heris; Sonia, Gina Aria; Nasir, Tatang Muh; Latifah, Leti; Nuroh, Laelatul (Attadib: Journal of Elementary Education, 2024)
Islamic Education Philosophy has an important role in shaping education in accordance with Islamic values. One of the important concepts in Islamic Education Philosophy is the purpose of life and society as the object of study. The purpose of human life in the view of Islam is to achieve perfection and happiness in his life, both in this world and in the hereafter. Meanwhile, society is also the object of study because humans are social creatures who cannot live alone. This study aims to analyze the implementation of the concept of the purpose of life and society as objects of study in the Philosophy of Islamic Education from the thoughts of Muslim philosophers as well as the conceptual implementation of the object of study in the curriculum with various philosophical approaches, namely synopsis, normative and inductive. This research uses a qualitative method with a literature study approach. The results of this study indicate that understanding and implementing the concept of the purpose of life and society according to the thoughts of Muslim philosophers in Islamic Education Philosophy can help develop a quality Islamic education curriculum that is in accordance with Islamic valuesTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//